ANALISIS PERMINTAAN AIR MINUM ISI ULANG DI KOTA PEKANBARU - Didik Prabowo; Tri Sukirno Putro; Lapeti Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the city of Pekanbaru in November 2014 to December 2016. The purpose of this study was to determine the factors that influence the demand for Drinking Water Refill in Pekanbaru.The data used in this study are primary data and secondary data analysis method is descriptive quantitative. The primary data obtained directly from the respondents that the people in the city of Pekanbaru and secondary data obtained from agencies and institutions such as the Central Bureau of Statistics and the City Health Office Pekanbaru. In this study population is all households that consume Water Recharge in the city of Pekanbaru, amounting to 240 888, where the number of samples taken was 100 respondents.The results showed that household income amounted to - 6.711% this means is that any increase household incomes by 1 level it will decrease the demand for drinking water refill - 6.711%, assuming other variables remain. Household members amounted to 0.821%.This means is that any increase in household members by 1 degree will increase the demand for drinking water refill of 0.821%, assuming other variables remain while the price of water amounted to 0.001%. What this means is that any increase in the price of water by 1 degree will increase demand for refill drinking water is 0,001, assuming other variables remain.Keywords : Demand Water Refill, Earnings, Household Members and Price